دراسة نسيجية مقارنة للكبد عند ثلاثة أنواع من الفقاريات (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
This present study aimed to perform a histological comparison of the liver in three types of vertebrates: Hyla savignyi, Hemidactylus turcicus, Testudo graeca. The results showed a structural similarity of the liver in the previous animals, with significant differences in the place of  hepatic cells and sinusoids and the  presence of the hepatic triad, furthermore,  it has been observed  that  hepatic cells are placed as glomeruli in the liver of  Hyla savignyi, and glomerular reticular in Hemidactylus turcicus; on the other hand, the hepatic cells in Testudo graeca are placed in format of glomerular corded around the central vein. moreover, The study also revealed  the absence of hepatic triad in both Hemidactylus turcicus and  Hyla savignyi ; Testudo graeca, in contrast, have hepatic triad. هدفت الدراسة الحالية إلى إجراء مقارنة نسيجية للكبد عند ثلاثة أنواع من الفقاريات: ضفدع الشجر Hyla savignyi، أبو بريص البحر المتوسط المنزلي Hemidactylus turcicus، السلحفاة مهمازية الورك Testudo graeca. أظهرت النتائج تشابهاً بنيوياً للكبد عند حيوانات الدراسة، مع وجود اختلافات ملحوظة في توضع الخلايا الكبدية والجيبانيات (أشباه الجيوب) ووجود الثالوث الكبدي، حيث لوحظ توضع الخلايا الكبدية بشكل كبيبات في كبد الضفدع، وكبيبي شبكي عند أبو بريص، أما عند السلحفاة فتتوضع الخلايا الكبدية بشكل كبيبي حبلي حول الوريد المركزي. كما كشفت الدراسة غياب الثالوث الكبدي عند أبو بريص وضفدع الشجر مقارنة مع السلحفاة مهمازية الورك.